Regulation of hyaluronan and versican deposition by growth factors in fibrosarcoma cell lines - Berdiaki, A.; Zafiropoulos, A.; Fthenou, E.; Katonis, P.; Tsatsakis, A.; Karamanos, N.K.; Tzanakakis, G.N. (Biochimica et biophysica acta, 2008)
Versican, a large chondroitin sulphate proteoglycan and hyaluronan (HA), a non-sulphated glycosaminoglycan are major constituents of the pericellular matrix. In many neoplastic tissues, changes in the expression of versican and HA affect tumour progression. Here, we analyse the synthesis of versican and hyaluronan by fibrosarcoma cells, and document how the latter is affected by PDGF-BB, bFGF and TGFB2, growth factors endogenously produced by these cells. Fibrosarcoma cell lines B6FS and HT1080 were utilised and compared with normal lung fibroblasts (DLF). The major versican isoforms expressed by DLF and B6FS cells were V0 and V1. Treatment of B6FS cells with TGFB2 showed a significant increase of V0 and V1 mRNAs. Versican expression in HT1080 cells was not significantly affected by any of the growth factors. In addition, TGFB2 treatment increased versican protein in DLF cells. HA, showed approximately a 2-fold and a 9-fold higher production in DLF cells compared to B6FS and HT1080 cells, respectively. In HT1080 cells, HA biosynthesis was significantly increased by bFGF, whereas, in B6FS cells it was increased by TGFB2 and PDGF-BB. Furthermore, analysis of HA synthases (HAS) expression indicated that HT1080 expressed similar levels of all three HAS isoforms in the following order: HAS2> HAS3> HAS1. bFGF shifted that balance by increasing the abundance of HAS1. The major HAS isoform expressed by B6FS cells was HAS2. PDGF-BB and TGFB2 showed the most prominent effects by increasing both HAS2 and HAS1 isoforms. In conclusion, these growth factors modulated, through upregulation of specific HAS isoforms, HA synthesis, secretion and net deposition to the pericellular matrix.